2021
DOI: 10.1093/ehjcvp/pvab052
|View full text |Cite
|
Sign up to set email alerts
|

An international audit of the management of dyslipidaemia and hypertension in patients with rheumatoid arthritis: results from 19 countries

Abstract: Aims To assess differences in estimated cardiovascular disease (CVD) risk among rheumatoid arthritis (RA) patients from different world regions. Further to evaluate the management and goal attainment of lipids and blood pressure (BP). Methods and results The SUrvey of CVD Risk Factors in patients with RA was conducted in 14503 patients from 19 countries during 2014–2019. The treatment goal for BP was <140/90 mmHg. CVD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…19,20 In an international audit involving 19 countries of the management of dyslipidaemia and hypertension in patients with RA, it was noted that the lipid target attainment was only 45% and 18% in the high and very high risk groups respectively and 62% had hypertension, but only approximately half of these patients were attaining target blood pressure. 21 In another study, atherosclerotic cardiovascular disease (ASCVD) was present in 26.7% of patients with RA and DM, compared with 11.6% without DM, indicating the need for effective control of risk factors. 22 Inertia in controlling these risk factors and providing adequate screening for cardiovascular illness results in poorer outcomes.…”
Section: Inertia In Addressing Comorbiditiesmentioning
confidence: 98%
“…19,20 In an international audit involving 19 countries of the management of dyslipidaemia and hypertension in patients with RA, it was noted that the lipid target attainment was only 45% and 18% in the high and very high risk groups respectively and 62% had hypertension, but only approximately half of these patients were attaining target blood pressure. 21 In another study, atherosclerotic cardiovascular disease (ASCVD) was present in 26.7% of patients with RA and DM, compared with 11.6% without DM, indicating the need for effective control of risk factors. 22 Inertia in controlling these risk factors and providing adequate screening for cardiovascular illness results in poorer outcomes.…”
Section: Inertia In Addressing Comorbiditiesmentioning
confidence: 98%
“…CVD prevention in patients with IJD is advocated and the European Alliance of Associations for Rheumatology (EULAR) advises routine CVD screening for patients with IJD 3. Despite increased awareness of excess CVD risk, management is often suboptimal and CVD risk factors are frequently non-recorded and undertreated in patients with IJD 16 17. Common CVD risk prediction models underestimate the risk of CVD in the context of IJD,18 a fact that accentuates the need for additional health measures to optimise CVD risk evaluation in this high-risk population 16.…”
Section: Introductionmentioning
confidence: 99%
“…Because hypertensive individuals often take multiple pills, they are sometimes reluctant to take additional lipid‐lowering drugs. It was recently reported that some hypertensive patients with dyslipidemia still did not have a cholesterol‐lowering drug even though they have hypertensive complications 22,23 . A group of patients treated with an ALR regimen (62.1% started taking statins) had a significant reduction of target LDL‐C compared to an AL‐treated group (74.8% vs 89.1%, p < .01), 16 suggesting that SPCs containing a statin could be an attractive treatment option to improve the lipid control in patients who are taking multiple pills by improving their drug adherence.…”
mentioning
confidence: 99%